Investigating The Impact Of Pragmatics On Communicative Competence Models: A Historical-descriptive Study - Naoua, Mohammed; Ghedeir, Brahim Mohammed (جامعة الوادي - University of Eloued, 2022)
This study attempts to explore the role of pragmatics in reinforcing the process of discourse production and comprehension. The paper starts with the delimitation of the scope of pragmatics and the identification of its main constituents, such as implicature, presupposition, speech acts, the context of situation, reference, deixis, and entailments. Then, it turns to the description of the way in which pragmatics has gradually been incorporated in three significant communicative competence models. In doing so, this paper incorporates the techniques of the historical-descriptive methods. The results of the study revealed that the integration of pragmatic elements in language analysis/teaching could contribute to the comprehension of speaker's/writer's implicated meaning.
article
Keywords: Context , Communicative Competence , Discourse , Implicature , Pragmatics , Speech Acts